2011
DOI: 10.1016/j.biomaterials.2010.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gel spun silk-based biomaterials in a murine model of bladder augmentation

Abstract: Currently, gastrointestinal segments are considered the gold standard for bladder reconstructive procedures. However, significant complications including chronic urinary tract infection, metabolic abnormalities, urinary stone formation, bowel dysfunction, and secondary malignancies are associated with this approach. Biomaterials derived from silk fibroin may represent a superior alternative due their robust mechanical properties, biodegradable features, and processing plasticity. In the present study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
81
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 53 publications
2
81
3
Order By: Relevance
“…11 In the present study, we aimed to use a bilayer scaffold based on poly-l-lactide/silk fibroin (PL-SF) for bladder augmentation. The inner porous layer of the scaffold was designed to promote cell proliferation and the second outer layer to serve as a barrier to fluid penetration.…”
mentioning
confidence: 99%
“…11 In the present study, we aimed to use a bilayer scaffold based on poly-l-lactide/silk fibroin (PL-SF) for bladder augmentation. The inner porous layer of the scaffold was designed to promote cell proliferation and the second outer layer to serve as a barrier to fluid penetration.…”
mentioning
confidence: 99%
“…The bladder was brought external to the body cavity and exposed. The dome of the bladder was incised 12,13 and a donor graft from the dome of a syngeneic, wild-type male mouse bladder, *5 mm in diameter, was sewn on with a running 8-0 Vicryl suture (Ethicon). The urethra was catheterized with a 24-gauge angiocatheter (BD Biosciences), and the bladder was inflated to verify a watertight anastomosis.…”
Section: Bladder Wall Transplantmentioning
confidence: 99%
“…5 However, a 50% rate of survival for mice postbladder transplant is consistent with other studies and is likely due to the technical challenge of creating a watertight anastomosis. 12 In addition, mice less than 5 months post-BMT exhibited only a 30% survival rate on bladder transplant. Thus, to achieve nearly 50% survival rate, we chose to use animals between 5 and 8 months post-BMT for these studies.…”
mentioning
confidence: 99%
“…We have previously reported the use of a bladder augmentation model in mice to determine the potential of silk fibroin-based scaffolds to mediate tissue regeneration and functional voiding characteristics. 11,12 Cystometric analyses of this model have shown that variations in structural and mechanical implant properties can influence the resulting urodynamic features of the tissue engineered bladders 11,12 . Positive correlations between the degree of matrixmediated tissue regeneration determined histologically and functional compliance and capacity evaluated by cystometry were demonstrated in this model 11,12 .…”
mentioning
confidence: 99%
“…11,12 Cystometric analyses of this model have shown that variations in structural and mechanical implant properties can influence the resulting urodynamic features of the tissue engineered bladders 11,12 . Positive correlations between the degree of matrixmediated tissue regeneration determined histologically and functional compliance and capacity evaluated by cystometry were demonstrated in this model 11,12 . These results therefore suggest that functional evaluations of biomaterial configurations in rodent bladder augmentation systems may be a useful format for assessing scaffold properties and establishing in vivo feasibility prior to large animal studies and clinical deployment.…”
mentioning
confidence: 99%